AB1229 SAFETY OF BIOSIMILAR ETANERCEPT IN THE TREATMENT OF RHEUMATIC DISEASES: DATA FROM THE MEXICAN ADVERSE EVENTS REGISTRY (BIOBADAMEX). (2nd June 2020) - Rivera Teran, V.; Pérez Rodríguez, M.; Alpizar-Rodriguez, D.; Irazoque-Palazuelos, F.; Carrilo, S.; Sicsik, S.; Vega-Morales, D.; Miranda, D.; Castillo, A.; Casasola, J. C.; Pacheco Tena, C. F.; Moctezuma, J. F.; et al.
Abstract : Background: Access to biosimilar drugs in Mexico started on 2014. Although biosimilar drugs safety has proved comparability to originator drugs on trials, information about its safety on real-life data is limited. Objectives: To compare safety in terms of adverse events of biosimilar etanercept (BEt) to originator etanercept (OEt) using information from the Mexican Adverse Events Registry (BIOBADAMEX). Methods: BIOBADAMEX is a Mexican cohort that collects the information of biologic and biosimilar drugs used in patients with rheumatic diseases in public and private practice since 2016. Patients enrolled are followed- up yearly. For this study we included patients from 18 to 65 years old who were or are currently in treatment with OEt or BEt and analyzed the frequency of adverse events (AE), the severity and the outcome of these. Baseline time was considered at enrolment to the cohort. We used logistic regression to analyze univariable and multivariable associations. Results: At the time of analysis a total of 119 have received treatment with OEt, 38 with BEt. Mean follow up time was 1.35 years. Rheumatoid arthritis (RA) was the most common disease for all the groups followed by ankylosing spondylitis (AS) and psoriatic arthritis (PsA). Both groups had similar baseline characteristics (Table 1 ). AE occurred in 4 (3.4%) patients with OEt and in 6 (15.8%) with BEt (OR 0.2, 95% CI 0.04-0.7). The most frequent AE in OEt group was allergic reaction, (2(2.5%) of patients), and infections were the most frequent AE in BEt group (2 (5.3%)). Of patients with BEt, 2(5.3%) had severe AE compared to none in the OEt (p=0.012). In the multivariable adjusted analysis comparing development of AE vs no AE including BEt, comorbidities and glucocorticoids, we found that use of BEt (OR 4.6, 95%CI 1.1-19.5) and presence of comorbidities (OR 4.6, 95%CI 1.01-20.5), were associated with AE. Use of glucocorticoids was not significantly associated. Conclusion: This preliminary study showed that AE with BEt were more frequent as well as more severe compared to AE presented with OEt in patients with rheumatic diseases using BIOBADAMEX data. Our study suggests that use of BEt and comorbidities are associated with the development of AE. Follow up and inclusion of more participants is going on and will allow us to perform further analyses. References: [1]Rugo HS et al. Future Oncol. 2019;15(7):777-790 [2]Moots RJ BioDrugs. 2018;32(3):193-199 Disclosure of Interests: Vijaya Rivera Teran: None declared, Marcela Pérez Rodríguez: None declared, Deshire Alpizar-Rodriguez: None declared, Fedra Irazoque-Palazuelos Consultant of: Bristol-Myers Squibb, Janssen, Pfizer Inc, Roche and UCB, Sandra Carrilo: None declared, Sandra Sicsik: None declared, David Vega-Morales: None declared, Dafhne Miranda: None declared, angel castillo: None declared, Julio Cesar Casasola: None declared, Cesar Francisco Pacheco Tena: None declared, José Francisco Moctezuma: None declared, Francisco Aceves: None declared, Aleni Paz: None declared, Sergio Duran Barragan: None declared, Leonor Barile: None declared, Natalia Santana: None declared, Daniel Xavier Xibille Friedmann Consultant of: Lilly, Abbvie, Speakers bureau: Lilly, Abbvie